1994
DOI: 10.1002/app.1994.070541310
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of crosslinking of random polymer network by rheological and equilibrium swelling data

Abstract: SYNOPSISThe transesterification reaction in the molten state of ester groups of ethylene vinyl acetate (EVA) copolymers and ethylene acrylic ester (EMA) copolymers has been used to crosslink the chains of this polymeric system. The relative EVA copolymers (or EMA copolymers) concentration dependence of the network formation by co-crosslinking of EVA/EMA miscible blends has been assessed. EVA/EMA networks were characterized by swelling experiments, rheological measurements, and determination of the extent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…In a previous study [18], it was found that c is n 2 dependent for the EVA/toluene system, according to…”
Section: Gel Fraction and Swelling Ratementioning
confidence: 95%
See 1 more Smart Citation
“…In a previous study [18], it was found that c is n 2 dependent for the EVA/toluene system, according to…”
Section: Gel Fraction and Swelling Ratementioning
confidence: 95%
“…Its amount of vinyl acetate (VA) was 28% by weight, corresponding to a molar composition of 10.6% of VA units. The number average molar mass and weight average molar mass of 19,000 g mol À1 and 53,500 g mol À1 , respectively, were measured by size exclusion chromatography in trichlorobenzene at 135.8 C [18]. EVA 2803 had a melting point of around 75 C and a zero shear viscosity of 1.0 Â 10 4 Pa s at 115 C.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Its amount of vinyl acetate units (VA) is 28% by weight [21,22], which corresponds to a molar composition of 10.6% of VA units. It presents a melting point around 75 8C.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Indeed, more precise determination requires that both loss and storage moduli are measured at several frequencies, but the present discussion of rheological experiments focuses on the storage and loss moduli crossover, as this crossover is generally close to the gel point for polymer network precursors [45,46].…”
Section: Crosslinking Kineticsmentioning
confidence: 99%